Afinidade, afetividade, organização: processos de mobilização de black blocs - Victor José Alves Fernandes; Yurij Castelfranchi (Ciências Sociais Unisinos)
On this paper, we investigate black bloc’s mobilization processes for protest events, based on semi-structured interviews and participant observation. In order to do so, firstly we localize black blocs in the field of autonomism, highlighting the autonomist cultural and identity plurality. Secondly, we proceed to map the analysis on black bloc’s mobilization processes in Brazil and abroad. Finally, we take on our interviews’ content analysis, provided with theoretical elements extracted from the expert literature on one hand and, on the other hand, with ethnographical experience. Our results converge into the creation of three interrelated types of black blocs’ mobilization, oriented by (a) the articulation of affinity groups; (b) previous and systematic bloc organization; and (c) the spontaneous bloc formation through the sharing of affective states and interaction on digital social networks.